Outcome of inflammatory response after normothermia during cardiopulmonary bypass surgery in infants with isolated ventricular septal defect - Dong Sub Kim; Sang In Lee; Sang Bum Lee; Myung Chul Hyun; Joon Yong Cho; Young Ok Lee (Korean Pediatric Society, 2014)
PurposeA recent study analyzing several cytokines reported that long cardiopulmonary bypass (CPB) time and long aortic cross clamp (ACC) time were accompanied by enhanced postoperative inflammation, which contrasted with the modest influence of the degree of hypothermia. In this present study, we aimed to examine the effect of CPB temperature on the clinical outcome in infants undergoing repair of isolated ventricular septal defect (VSD).MethodsOf the 212 infants with isolated VSD who underwent open heart surgery (OHS) between January 2001 and December 2010, 43 infants were enrolled. They were classified into 2 groups: group 1, infants undergoing hypothermic CPB (26℃-28℃; n=19) and group 2, infants undergoing near-normothermic CPB (34℃-36℃; n=24).ResultsThe age at the time of the OHS, and number of infants aged<3 months showed no significant differences between the groups. The CPB time and ACC time in group 1 were longer than those in group 2 (88 minutes vs. 59 minutes, P=0.002, and 54 minutes vs. 37 minutes, P=0.006 respectively). The duration of postoperative mechanical ventilation was 1.6 days in group 1 and 1.8 days in group 2. None of the infants showed postoperative neurological and developmental abnormalities. Moreover, no postoperative differences in the white blood cell count and C-reactive protein levels were noted between two groups.ConclusionThis study revealed that hypothermic and near-normothermic CPB were associated with similar clinical outcomes and inflammatory reactions in neonates and infants treated for simple congenital heart disease.